(untitled) (Revista Apotheke, 2018)
The present article sought to present the theoretical-practical production carried out during the course "About Being an Artist Professor", taught by the teacher Phd. Jociele Lampert, studied by the student Dt. Paula Rodrigues during the second half of 2018 in the Postgraduate Program in Visual Arts at the UDESC Arts Center. With regard to the analysis of the student’s production, it was first intended to present the discipline and, subsequently, the work developed with emphasis on experimentation, the creative process and the knowledge learned, as well as the final result of the work and the reflection provided for them.